Religion after Religion : Gershom Scholem, Mircea Eliade, and Henry Corbin at Eranos. - Wasserstrom, Steven M. (Princeton University Press, 2001)
By the end of World War II, religion appeared to be on the decline throughout the United States and Europe. Recent world events had cast doubt on the relevance of religious belief, and modernizing trends made religious rituals look out of place. It was in this atmosphere that the careers of Scholem, Eliade, and Corbin--the twentieth century's legendary scholars in the respective fields of Judaism, History of Religions, and Islam--converged and ultimately revolutionized how people thought about religion. Between 1949 and 1978, all three lectured to Carl Jung's famous Eranos circle in Ascona, Sw.